Dechlorination of Four Commercial Polychlorinated Biphenyl Mixtures (Aroclors) by Anaerobic Microorganisms from Sediments - Quensen, John F. (1990)
The rate, extent, and pattern of dechlorination of four Aroclors by inocula prepared from two polychlorinated biphenyl (PCB)-contaminated sediments were compared. The four mixtures used, Aroclors 1242, 1248, 1254, and 1260, average approximately three, four, five, and six chlorines, respectively, per biphenyl molecule. All four Aroclors were dechlorinated with the loss of meta plus para chlorines ranging from 15 to 85%. Microorganisms from an Aroclor 1242-contaminated site in the upper Hudson River dechlorinated Aroclor 1242 to a greater extent than did microorganisms from Aroclor 1260-contaminated sediments from Silver Lake, Mass. The Silver Lake inoculum dechlorinated Aroclor 1260 more rapidly than the Hudson River inoculum did and showed a preferential removal of meta chlorines. For each inoculum the rate and extent of dechlorination tended to decrease as the degree of chlorination of the Aroclor increased, especially for Aroclor 1260. The maximal observed dechlorination rates were 0.3, 0.3, and 0.2 μg-atoms of Cl removed per g of sediment per week for Aroclors 1242, 1248, and 1254, respectively. The maximal observed dechlorination rates for Hudson River and Silver Lake organisms for Aroclor 1260 were 0.04 and 0.21 μg-atoms of Cl removed per g of sediment per week, respectively. The dechlorination patterns obtained suggested that the Hudson River microorganisms were more capable than the Silver Lake organisms of removing the last para chlorine. These results suggest that there are different PCB-dechlorinating microorganisms at different sites, with characteristic specificities for PCB dechlorination.